Resolving large financial intermediaries: banks versus housing enterprises - Robert A. Eisenbeis; W. Scott Frame; Larry D. Wall (Federal Reserve Bank of Atlanta, 2004)
This paper examines the policy issues with respect to resolving the possible failure of housing enterprises Fannie Mae or Freddie Mac. The authors compare and contrast these issues with those raised in the context of large bank failures and also identify important differences in the extant supervisory authorities. Based on these discussions, they offer a number of policy suggestions designed to minimize the cost of resolution and protect taxpayers from loss should a large bank or housing enterprise fail.
Keywords: 330; Hypothekenbank; Hypothek; Bankinsolvenz; Bankenaufsicht; USA